Hydrocephalus due to marked enlargement of spinal roots in a patient with chronic inflammatory demyelinating polyradiculoneuropathy. (13th October 2020) - Iwasaki, A.; Kokubun, N.; Funakoshi, K.; Hirata, K.; Suzuki, K.
Abstract : Background: Hydrocephalus or papilledema has rarely been reported in patients with chronic inflammatory demyelinating polyradiculoneuropathy (CIDP). Methods: We report a 65‐year‐old woman with a 12‐year history of CIDP presenting with progressive dementia, hallucination and deterioration of gait. Results: Neurological examination revealed cognitive impairment, symmetric proximal and distal weakness with areflexia and muscle atrophy in the distal four limbs. The cerebrospinal fluid examination showed marked elevation of protein concentration. Magnetic resonance imaging revealed hydrocephalus and marked enlarged cervical and lumbar roots and plexus. The cervical cord and cauda equina were compressed by the swollen roots. A ventriculoperitoneal shunt resulted in reduction of the ventricles size along with improvement of her cognitive impairment. Conclusion: In our patient with CIDP, hydrocephalus was likely caused by hypertrophic nerve roots. Our findings suggest that CIDP patients with pronounced hypertrophic nerve roots require careful observation.